a) The given equation can be written as
"(D^2 - 1)y = \\frac{2}{1+e^x}"
The auxiliary equation is
"m^2 - 1 = 0\\\\\nm = \\pm 1"
The complimentary function is
"C.F = c_{1}e^x + c_{2}e^{-x}= c_{1}f_{1} + c_{2}f_{2}," where "f_{1} = e^x, f_{2} = e^{-x}"
The particular integral is = "Pf_{1}+Qf_{2}", where
"P = -\\displaystyle\\int \\dfrac{f_{2}g(x)}{W(f_{1},f_{2})}dx, Q = \\displaystyle\\int \\dfrac{f_{1}g(x)}{W(f_{1},f_{2})}dx"
where, "g(x) = \\dfrac{2}{1+e^{x}}\\\\"
"W(f_{1},f_{2}) = f_{1}f'_{2} - f'_{1}f_{2} = e^{x}(-e^{-x}) - e^{x}e^{-x} = -2"
"P = -\\displaystyle\\int \\dfrac{2e^{-x}}{-2(1+e^x)}dx = \\displaystyle\\int \\dfrac{e^{-x}}{1+e^{x}}dx\\\\=\\displaystyle\\int \\dfrac{e^{-2x}}{1+e^{-x}}dx"
Put "u = 1+e^{-x}" , then "du = -e^{-x}dx"
"dx = -\\dfrac{dy}{y-1}" .Therefore,
"P = \\displaystyle\\int \\dfrac{(y-1)^2~(-dy)}{y(y-1)} = -\\displaystyle\\int \\dfrac{y-1}{y}dy\\\\= \\displaystyle\\int (\\dfrac{1}{y} - 1)dy = \\ln y - y \\\\ P= \\ln (1+e^{-x}) -1-e^{-x}"
"Pf_{1} = e^{x}(\\ln(1+e^{-x}) - e^{-x}-1) \\\\= e^{x}(\\ln(1+e^{-x})-1)-1"
"Q = \\displaystyle\\int \\dfrac{2e^{x}}{-2(1+e^{x})}dx = -\\displaystyle\\int \\dfrac{e^{x}}{1+e^{x}}dx\\\\ Q=-\\ln(1+e^{x})\\\\ Qf_{2} = -e^{-x}\\ln(1+e^{x})\\\\\n\\text{Hence,} \\\\\nP.I = e^{x}(\\ln(1+e^{-x})-1)- e^{-x}\\ln(1+e^{x})-1."
The complete solution is
"y = C.F.+P.I = e^{x}(c_{1} + \\ln(1+e^{-x}) - 1) + e^{-x}(c_{2} - \\ln(1+e^{x})) - 1"
b) The given equation can be written as, "(D^{2} + D - 2)y = -6\\sin2x-18\\cos2x, y(0) = 2,y'(0)=2."
The auxiliary equation is,
"m^{2} + m -2 =0 \\\\(m+2)(m-1)=0\\\\ m = -2,1\\\\ C.F = c_{1}e^{-2x} + c_{2}e^{x}\\\\"
"P.I = \\dfrac{1}{D^{2}+D-2}(-6\\sin2x-18\\cos2x)\\\\\n=-6 \\dfrac{1}{D^{2}+D-2}(\\sin2x+3\\cos2x)\\\\\n=-6(\\dfrac{1}{D^{2}+D-2}(\\sin2x) + \\dfrac{1}{D^{2}+D-2}(3\\cos2x))\\\\\n=-6(\\dfrac{1}{-4+D-2}(\\sin2x) + 3\\dfrac{1}{-4+D-2}(\\cos2x))~~(Replace~ D^{2}~ by -4)\\\\\n=-6(\\dfrac{1}{-6+D}(\\sin2x) + 3\\dfrac{1}{-6+D}(\\cos2x))\\\\\n=6(\\dfrac{1}{6-D}(\\sin2x) + 3\\dfrac{1}{6-D}(\\cos2x))\\\\\n=6(\\dfrac{6+D}{36-D^{2}}(\\sin2x) + 3\\dfrac{6+D}{36-D^{2}}(\\cos2x))\\\\\n=\\dfrac{3}{20}(6+D)(\\sin2x+3\\cos2x)~~(Replace ~D^{2}~by -4)\\\\\n=\\dfrac{3}{20}(6\\sin2x + 18\\cos2x)+D(\\sin2x+3\\cos2x)\\\\\n=\\dfrac{3}{20}(6\\sin2x + 18\\cos2x +2\\cos2x-6\\sin2x)\\\\\nP.I=3\\cos2x"
The complete solution is
"y(x)= c_{1}e^{-2x}+c_{2}e^{x}+3\\cos2x"
Given the initial conditions, "y(0)=2, y'(0)=2." We get,
"2=y(0)= c_{1}+c_{2}+3\\\\ c_{1}+c_{2} = -1\\\\\nNow, y'(x) = -2c_{1}e^{-2x}+c_{2}e^{x}-6\\sin2x\\\\\n2=y'(0) = -2c_{1}+c_{2}\\\\ -2c_{1}+c_{2} = 2\\\\"
Solving for "c_{1},c_{2}" we get, "c_{1} = -1, c_{2} = 0."
Thus, the complete solution becomes,
"y(x) = 3\\cos2x-e^{-2x}"
Comments
Leave a comment